Highly water-absorbent resin and method for producing same

By introducing acidic groups and internal crosslinking agents into the high-water absorption resin, forming a bridged polymer and crosslinking layer on the surface, the problems of slow liquid absorption speed and poor moisture retraction performance are solved, and a high-water absorption resin with fast water absorption and excellent moisture retraction performance are achieved.

JP2025503265APending Publication Date: 2025-01-30LG CHEM LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2024544997
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-11-16
Filing Date
2023-11-16
Publication Date
2025-01-30

AI Technical Summary

Technical Problem

The existing high-water absorption resins do not contain wood pulp, and the liquid absorption speed is slow and the moisture reflux performance is poor, making it difficult to meet the demand for thin sanitary products.

Method used

By preparing a high water absorption resin containing acid groups, the bridge polymer is formed using an internal crosslinking agent and an additional crosslinking layer is formed on the surface, controlling the particle size and density, ensuring rapid water absorption and good moisture reflux performance.

Benefits of technology

It achieves rapid water absorption and excellent moisture reflux performance of high water-absorbing resin without wood pulp, meeting the requirements of thin sanitary products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025503265000001
    Figure 2025503265000001
  • Figure 2025503265000002
    Figure 2025503265000002
  • Figure 2025503265000003
    Figure 2025503265000003
Patent Text Reader

Abstract

The present invention relates to a superabsorbent resin and a method for producing the same, and more specifically to a superabsorbent resin that has excellent rewet properties and excellent water absorption speed and water absorption performance even without containing pulp, and a method for producing the same.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims the benefit of priority based on Korean Patent Application No. 10-2022-0153918 dated November 16, 2022 and Korean Patent Application No. 10-2023-0159227 dated November 16, 2023, and all contents disclosed in the documents of said Korean patent applications are incorporated herein by reference.

[0002] The present invention relates to a superabsorbent resin and a method for producing the same, and more specifically to a superabsorbent resin that has excellent rewet properties and excellent water absorption speed and water absorption performance even without containing pulp, and a method for producing the same. [Background technology]

[0003] Super absorbent polymer (SAP) is a synthetic polymeric substance that has the ability to absorb 500 to 1,000 times its own weight in water, and each developer has a different name for it, such as SAM (Super Absorbency Material), AGM (Absorbent Gel Material), etc. Such super absorbent polymers first came into practical use as sanitary products, and are now widely used as soil rehydration agents for gardening, water-stopping materials for civil engineering and construction, seedling sheets, freshness-preserving agents in the food distribution field, and materials for packs.

[0004] Such superabsorbent polymers are widely used in the field of sanitary materials, such as diapers and sanitary napkins. In the sanitary materials, the superabsorbent polymers are generally contained in a dispersed state in the pulp. However, in recent years, efforts have been made to provide sanitary materials, such as diapers, with thinner thicknesses, and as part of these efforts, the pulp content has been reduced, or even going a step further, the development of so-called pulpless diapers, which do not use pulp at all, has been actively promoted.

[0005] In this way, in sanitary materials such as pulpless diapers where the pulp content is reduced or no pulp is used, the absorption of liquids such as urine becomes slower and the rewet performance deteriorates. However, since a superabsorbent polymer must not only function as an absorbent that absorbs liquids but also as pulp, it is required to exhibit high water absorption performance and fast water absorption speed.

[0006] This has led to a continuing demand for the development of superabsorbent resins that have excellent rewetting properties while maintaining the basic water absorption performance and fast water absorption rate of superabsorbent resins. Summary of the Invention [Problem to be solved by the invention]

[0007] The present invention relates to a highly water-absorbent resin that has excellent rewet properties and excellent water absorption speed and water absorption performance even without containing pulp, and a method for producing the same. [Means for solving the problem]

[0008] In order to solve the above problems, the present invention provides A base resin containing an acidic group, at least a portion of which has been neutralized, comprising a crosslinked polymer of an acrylic acid monomer and an internal crosslinking agent; and A superabsorbent resin comprising a surface cross-linked layer formed on the base resin and in which the cross-linked polymer is additionally cross-linked via a surface cross-linking agent, The superabsorbent resin is 1) The water retention capacity (CRC) measured by EDANA NWSP241.0.R2(15) is 32 g / g to 40 g / g; 2) The water-soluble component after swelling for 16 hours as measured by EDANA NWSP270.0.R2(15) is 10% by weight or less; 3) The water absorption speed (vortex time) measured by the vortex method is 30 seconds or less; 4) Bulk density measured according to EDANA NWSP251.0.R2(15) is 0.55 g / ml or more and 0.65 g / ml or less. A highly water-absorbent resin is provided.

[0009] The present invention also provides a method for producing a method for manufacturing a semiconductor device comprising the steps of: A step (step 1) of forming a hydrogel polymer by polymerizing a monomer composition including an acrylic acid monomer having an acid group, at least a portion of which has been neutralized, an internal crosslinking agent, an initiator, and hydrophobic particles; drying the hydrous gel polymer to form a base resin powder (Step 2); a first grinding step (step 3) of grinding the base resin powder so that the powder contains particles having a particle size of 710 μm or more at 50% by weight or more; A second pulverization step (step 4) of pulverizing the base resin powder subjected to the first pulverization step so that the powder contains particles having a particle size of 710 μm or more in an amount of 10% by weight or less; and Step 5: crosslinking the surface of the base resin in the presence of a surface crosslinking agent; A method for producing a superabsorbent resin is provided. Effect of the Invention

[0010] According to the present invention, by controlling the content of particles by particle size through pulverization to limit the bulk density to a certain range, it is possible to provide a superabsorbent resin that has a water absorption speed and water absorption performance equivalent to or superior to conventional superabsorbent resins even without containing pulp, and has excellent rewet properties. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The terms used in this specification are merely used to describe exemplary embodiments and are not intended to limit the present invention. A singular expression includes a plural expression unless the context clearly indicates otherwise. In this specification, the terms "include", "comprise", "have" and the like are intended to specify the presence of an implemented feature, step, component, or combination thereof, and should be understood not to preclude the possibility of the presence or addition of one or more other features, steps, components, or combinations thereof.

[0012] Although the present invention can be modified in various ways and has various forms, specific embodiments are exemplified and described in detail below. However, it is not intended to limit the present invention to the specific disclosed embodiments, and it should be understood that the present invention includes all modifications, equivalents, and alternatives falling within the spirit and technical scope of the present invention.

[0013] Furthermore, the terminology used herein is for the purpose of referring to particular embodiments only and is not intended to limit the present invention, and the singular forms used herein include the plural forms unless the language clearly indicates otherwise.

[0014] The term "polymer" or "polymeric polymer" used in the present specification means a state in which an acrylic acid monomer, which is a water-soluble ethylenically unsaturated monomer, is polymerized, and can include all water content ranges or particle size ranges. Among the above polymers, a polymer having a water content (water content) of about 40% by weight or more in a state after polymerization and before drying can be called a hydrogel polymer, and particles of such a hydrogel polymer that have been crushed and dried can be called a crosslinked polymer.

[0015] In addition, the term "superabsorbent resin particles" refers to a particulate material including a crosslinked polymer obtained by polymerizing an acrylic acid-based monomer having acidic groups and at least a portion of the acidic groups being neutralized, and crosslinking the monomer with an internal crosslinking agent.

[0016] Also, the term "super absorbent polymer" refers to a crosslinked polymer obtained by polymerizing an acrylic acid monomer containing acidic groups and at least a portion of which has been neutralized, or a powder-like base resin made of super absorbent polymer particles obtained by pulverizing the crosslinked polymer, depending on the context, or is used to encompass all of the crosslinked polymers or base resins that have been subjected to additional processes, such as surface crosslinking, regranulation into fine powder, drying, pulverization, classification, etc., to be in a state suitable for commercialization. Therefore, the term "super absorbent polymer" can be interpreted as including a plurality of super absorbent polymer particles.

[0017] The term "average diameter" of the pores means the median of the longest diameters of the pores contained in the superabsorbent polymer, in order to reduce the influence of outliers compared to the simple average.

[0018] With the increasing demand for thin and light diapers, research into pulpless diapers is underway. In pulpless diapers, super absorbent polymer (SAP) replaces the role of pulp, but an absorbent core made of 100% super absorbent polymer has the problem of slow urine absorption and poor rewet performance. Therefore, a super absorbent polymer with excellent rewet performance, as well as other good water absorption properties and water absorption speed, must be developed.

[0019] Therefore, the inventors have confirmed that a superabsorbent resin having a specific range of bulk density, which has been subjected to foaming and two grinding processes using hydrophobic particles in a neutralization liquid, has excellent water absorption performance and water absorption speed, and also has improved rewetting performance, thereby completing the present invention.

[0020] Hereinafter, the superabsorbent polymer and the method for producing the superabsorbent polymer will be described in detail step by step according to specific embodiments of the present invention.

[0021] Super absorbent resin According to one embodiment, the superabsorbent resin includes a base resin including a crosslinked polymer of an acrylic acid monomer and an internal crosslinking agent, the crosslinked polymer including an acidic group and at least a portion of the acidic group being neutralized; and a surface crosslinked layer formed on the base resin, the crosslinked polymer being additionally crosslinked via a surface crosslinking agent.

[0022] The superabsorbent polymer may have a water retention capacity (CRC) of 32 g / g to 40 g / g measured according to EDANA NWSP241.0.R2(15). Preferably, the water retention capacity of the superabsorbent polymer may be 32 g / g or more, 33 g / g or more, or 33.4 g / g or more, and 40 g / g or less, 39 g / g or less, or 38.7 g / g or less. The higher the water retention capacity of the superabsorbent polymer, the higher the water absorption capacity of the diaper when used in the diaper, and the less the superabsorbent polymer can be used. However, it is difficult to achieve a water retention capacity of 40 g / g or more while maintaining a high water absorption rate, but when the water retention capacity of the superabsorbent polymer is 32 g / g to 40 g / g, it is possible to obtain physical properties of a satisfactory level in terms of both water retention capacity and water absorption rate.

[0023] The superabsorbent polymer may have a water-soluble component of 10% by weight or less after swelling for 16 hours as measured according to EDANA NWSP270.0.R2(15).Preferably, the water-soluble component of the superabsorbent polymer may have a water-soluble component of 9% by weight or less, 8% by weight or less, or 7.7% by weight or less, and 1% by weight or more, 3% by weight or more, or 5% by weight or more after swelling for 16 hours.

[0024] The superabsorbent polymer may have a water absorption rate (vortex time) of 30 seconds or less by the vortex method. Preferably, it may be 29 seconds or less or 28 seconds or less. The smaller the water absorption rate, the better. The lower limit of the water absorption rate is theoretically 0 seconds, but it may be 10 seconds or more, 15 seconds or more, 18 seconds or more, 20 seconds or more, 21 seconds or more, or 22 seconds or more. If the water absorption rate of the superabsorbent polymer exceeds 30 seconds, there is a problem that the rewetting performance is also reduced, and a superabsorbent polymer having a water absorption rate of less than 10 seconds is difficult to manufacture. At this time, the method for measuring the water absorption rate of the superabsorbent polymer will be described in more detail in the experimental examples described below.

[0025] The bulk density of the superabsorbent polymer, as measured by EDANA NWSP251.0.R2(15), may be 0.55 g / ml or more and 0.65 g / ml or less. Preferably, the bulk density of the superabsorbent polymer is 0.56 g / ml or more, 0.57 g / ml or more, or 0.58 g / ml or more, and 0.63 g / ml or less, 0.62 g / ml or less, or 0.60 g / ml or less.

[0026] A high water absorption rate means that the specific surface area of ​​the particles is large, so superabsorbent resin particles with a high water absorption rate have the characteristic of having a low bulk density. If the bulk density is low, a large amount of superabsorbent resin needs to be added, which increases production costs, so it is better for the bulk density to be appropriately high, but when considering the balance with the water absorption rate, the range of 0.55 g / ml to 0.65 g / ml is appropriate. If the bulk density is high and exceeds 0.65 g / ml, flowability may decrease.

[0027] Meanwhile, the acrylic acid monomer is a compound represented by the following Chemical Formula 1:

[0028] [Chemical formula 1] R 1 -COOM 1

[0029] In the above Chemical Formula 1, R1 is an alkyl group having 2 to 5 carbon atoms and containing an unsaturated bond, M 1 is a hydrogen atom, a monovalent or divalent metal, an ammonium group, or an organic amine salt.

[0030] Preferably, the acrylic acid monomer includes at least one selected from the group consisting of acrylic acid, methacrylic acid, and their monovalent metal salts, divalent metal salts, ammonium salts, and organic amine salts.

[0031] Here, the acrylic acid monomer may have an acidic group, and at least a part of the acidic group may be neutralized. Preferably, the monomer may be partially neutralized with an alkaline substance such as sodium hydroxide, potassium hydroxide, or ammonium hydroxide. In this case, the neutralization degree of the acrylic acid monomer may be 40 to 95 mol%, 40 to 80 mol%, or 45 to 75 mol%. The range of the neutralization degree can be adjusted according to the final physical properties. However, if the neutralization degree is too high, the neutralized monomer may precipitate, making it difficult to smoothly proceed with polymerization, and conversely, if the neutralization degree is too low, not only the water absorption of the polymer may be greatly reduced, but also the polymer may exhibit properties similar to elastic rubber, which are difficult to handle.

[0032] The concentration of the acrylic acid monomer may be about 20 to about 60% by weight, preferably about 40 to about 50% by weight, based on the monomer composition containing the raw material of the superabsorbent resin and the solvent, or may be an appropriate concentration taking into consideration the polymerization time and reaction conditions, etc. However, if the concentration of the monomer is too low, the yield of the superabsorbent resin may be low, causing problems in terms of economy, and conversely, if the concentration is too high, problems may occur in the process, such as partial precipitation of the monomer or reduced efficiency in pulverizing the polymerized hydrogel polymer, resulting in reduced physical properties of the superabsorbent resin.

[0033] In addition, the term "internal crosslinking agent" used in this specification is a term used to distinguish it from a surface crosslinking agent for crosslinking the surface of superabsorbent resin particles described later, and plays a role in crosslinking and polymerizing the unsaturated bonds of the water-soluble ethylenically unsaturated monomer described above. The crosslinking in this step is performed without distinction between the surface and the inside, but when the surface crosslinking process of the superabsorbent resin particles described later is performed, the particle surface of the finally produced superabsorbent resin has a structure crosslinked by the surface crosslinking agent, and the inside has a structure crosslinked by the internal crosslinking agent.

[0034] As the internal crosslinking agent, any compound can be used as long as it can introduce crosslinking during polymerization of the acrylic unsaturated monomer.Specifically, as the internal crosslinking agent, a crosslinking agent having one or more functional groups that can react with the water-soluble substituent of the acrylic unsaturated monomer and one or more ethylenic unsaturated groups; or a crosslinking agent having two or more functional groups that can react with the water-soluble substituent of the monomer and / or the water-soluble substituent formed by hydrolysis of the monomer can be used.

[0035] As the internal crosslinking agent, any compound can be used as long as it can introduce crosslinking during polymerization of the acrylic unsaturated monomer.Specifically, as the internal crosslinking agent, a crosslinking agent having one or more functional groups that can react with the water-soluble substituent of the acrylic unsaturated monomer and one or more ethylenic unsaturated groups; or a crosslinking agent having two or more functional groups that can react with the water-soluble substituent of the monomer and / or the water-soluble substituent formed by hydrolysis of the monomer can be used.

[0036] The internal crosslinking agent may be an epoxy compound or a polyethylene glycol-based polymer. Non-limiting examples of the internal crosslinking agent include N,N'-methylenebisacrylamide, trimethylpropane tri(meth)acrylate, ethylene glycol di(meth)acrylate, polyethylene glycol (meth)acrylate, polyethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, polypropylene glycol (meth)acrylate, butanediol di(meth)acrylate, butylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, hexanediol di(meth)acrylate, triethylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, dipentaerythritol pentaacrylate, glycerin tri(meth) ... acrylate, pentaerythritol tetraacrylate, and other acrylate-based compounds; ethylene glycol diglycidyl ether, diethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, tripropylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, neopentyl glycol diglycidyl ether, 1,6-hexanediol diglycidyl ether, polytetramethylene glycol diglycidyl ether, glycerol diglycidyl ether, glycerol triglycidyl ether, diglycerol polyglycidyl ether, polyglycerol polyglycidyl ether, and other epoxy-based compounds; triarylamine; propylene glycol; glycerin; or polyfunctional crosslinkers such as ethylene carbonate, which may be used alone or in combination of two or more, but are not limited thereto.

[0037] According to one embodiment, the internal crosslinking agent may be an epoxy-based compound. For example, the internal crosslinking agent may be a polyfunctional epoxy compound having a valence of 2 or more, such as ethylene glycol diglycidyl ether. In this case, the foaming agent can be stably foamed by the hydrophobic particles.

[0038] In the monomer composition, the internal crosslinking agent can be used in an amount of 0.01 to 5 parts by weight based on 100 parts by weight of the acrylic acid monomer. For example, the internal crosslinking agent can be used in an amount of 0.01 parts by weight or more, 0.05 parts by weight or more, 0.1 parts by weight or more, or 0.15 parts by weight or more and 5 parts by weight or less, 3 parts by weight or less, 2 parts by weight or less, 1 part by weight or less, or 0.7 parts by weight or less based on 100 parts by weight of the water-soluble ethylenically unsaturated monomer. If the content of the internal crosslinking agent is too low, crosslinking may not occur sufficiently, making it difficult to achieve strength above an appropriate level, and if the content of the internal crosslinking agent is too high, the internal crosslinking density may increase, making it difficult to achieve the desired water retention ability.

[0039] The crosslinking polymerization of the water-soluble ethylenically unsaturated monomer in the presence of such an internal crosslinking agent may be carried out by thermal polymerization, photopolymerization or hybrid polymerization in the presence of a polymerization initiator and, if necessary, a thickener, a plasticizer, a storage stabilizer, an antioxidant, etc., the details of which will be described later.

[0040] In addition, the superabsorbent resin further includes a surface cross-linked layer formed by additionally cross-linking the cross-linked polymer contained in the base resin via a surface cross-linking agent on at least a part of the surface of the base resin, in order to increase the surface cross-linking density of the superabsorbent resin. When the superabsorbent resin further includes a surface cross-linked layer as described above, the superabsorbent resin has a structure in which the cross-linking density is higher on the outside than on the inside.

[0041] As the surface cross-linking agent, any surface cross-linking agent that has been used in the manufacture of conventional superabsorbent resins can be used without any particular limitation.For example, the surface cross-linking agent can include one or more selected from the group consisting of polyhydric alcohol compounds, polyfunctional epoxy compounds, polyamine compounds, haloepoxy compounds, condensation products of haloepoxy compounds, oxazoline compounds and alkylene carbonate compounds.

[0042] Specifically, examples of the polyhydric alcohol compound that can be used include mono-, di-, tri-, tetra- or polyethylene glycol, monopropylene glycol, 1,3-propanediol, dipropylene glycol, 2,3,4-trimethyl-1,3-pentanediol, polypropylene glycol, glycerol, polyglycerol, 2-butene-1,4-diol, 1,4-butanediol, 1,3-butanediol, 1,5-pentanediol, 1,6-hexanediol, and 1,2-cyclohexanedimethanol.

[0043] The polyfunctional epoxy compound may be ethylene glycol diglycidyl ether or glycidol.

[0044] The polyamine compound may be ethylenediamine, diethylenetriamine, triethylenetetraamine, tetraethylenepentamine, pentaethylenehexamine, polyethyleneimine, polyamidepolyamine, or the like.

[0045] Furthermore, the haloepoxy compound may be epichlorohydrin, epibromohydrin, α-methylepichlorohydrin, or the like.

[0046] As the oxazoline-based compound, mono-, di- or polyoxazolidinones can be used.

[0047] As the alkylene carbonate compound, ethylene carbonate, propylene carbonate, glycerol carbonate, or the like can be used.

[0048] More specifically, the surface cross-linking agent may be one of the above-mentioned surface cross-linking agents used alone or in combination with each other. As an example, an alkylene carbonate compound such as ethylene carbonate may be used as the surface cross-linking agent.

[0049] Meanwhile, the superabsorbent polymer may contain 10% by weight or less of particles having a particle size of 710 μm to 850 μm. Also, the superabsorbent polymer may contain 10% by weight or less of particles having a particle size of 150 μm or less. The particle size of the superabsorbent polymer particles may be measured according to the European Disposables and Nonwovens Association (EDANA) standard EDANA WSP220.3 method.

[0050] If the content of particles having a particle size of 710 μm to 850 μm is high, exceeding 10% by weight, the thin pulpless diaper may feel hard and have poor comfort when worn, and the water absorption rate may also decrease. Also, if the content of particles having a particle size of 150 μm or less exceeds 10% by weight, there is a disadvantage that a large amount of fine powder may cause filter clogging problems during processing, and the working environment may also become poor.

[0051] On the other hand, the rewet value measured for a pulpless absorbent material containing the superabsorbent polymer may be 1 g or less. Preferably, the rewet value is 0.1 g or more, 0.3 g or more, 0.5 g or more, or 0.7 g or more, and may be 1 g or less, 0.95 g or less, or 0.94 g or less.

[0052] The rewet value can be measured by producing a pulpless absorbent material containing a highly absorbent polymer and measuring the rewet value of the absorbent material. A specific method for producing and measuring the rewet value of the pulpless absorbent material is as follows.

[0053] 0.3 g of adhesive (product name: FLC7228AZP, manufacturer: HB Fuller) (adhesive layer) is uniformly applied on a first nonwoven fabric (product name: Softhann (registered trademark), manufacturer: Sambo) with a size of 350 mm x 100 mm using a hot melt sprayer, and then 4.5 g of the superabsorbent resin is uniformly applied at a feed rate of 2 g / s to prepare a first coating layer of superabsorbent resin. 0.3 g of adhesive is applied thereon to prepare a first coating layer of adhesive. Thereafter, the manufacturing process of the first coating layer of superabsorbent resin and the first coating layer of adhesive is repeated two more times to prepare a second coating layer of superabsorbent resin, a second coating layer of adhesive, a third coating layer of superabsorbent resin, and an adhesive layer, and then a second nonwoven fabric (product name: Softhann (registered trademark), manufacturer: Sambo) is attached to prepare an absorbent. The amount of adhesive used in each adhesive layer was the same at 0.3 g, and the amount of superabsorbent polymer used in each superabsorbent polymer layer was the same at 4.5 g.

[0054] Then, 85 mL of 0.9 wt % sodium chloride solution (physiological saline) is injected into the center of the absorbent (size 350 mm x 100 mm). After 15 minutes, a weight is placed on the absorbent and 85 mL of physiological saline is injected again at the same position while applying a pressure of 0.42 psi. After 15 minutes, the weight placed on the absorbent is temporarily removed, and then a paper (300 gsm filter paper) of size 300 mm x 90 mm is placed on the absorbent, and the weight is placed on the paper again to position the paper between the absorbent and the weight. After 2 minutes, the amount of salt water seeping out of the absorbent into the paper is measured, and the rewet amount (g) is calculated according to the following formula 1.

[0055] [Formula 3] Rewet amount (g) = W6 (g) - W5 (g)

[0056] In the above formula 3, W5 (g) is the initial weight of the paper, and W6 (g) is the weight of the paper that absorbs the liquid that seeps out of the absorbent body under a load (0.42 psi) for 2 minutes after injecting saline into the absorbent body with and without pressure.

[0057] Manufacturing method of superabsorbent resin The superabsorbent resin can be manufactured by the steps of: forming a hydrogel polymer by polymerizing a monomer composition including an acrylic acid monomer having an acid group and at least a part of the acid group being neutralized, an internal crosslinking agent, an initiator, and hydrophobic particles (step 1); drying the hydrogel polymer to form a base resin powder (step 2); a first grinding step (step 3) of grinding the base resin powder so that it contains 50% by weight or more of particles having a particle size of 710 μm or more; a second grinding step (step 4) of grinding the base resin powder subjected to the first grinding step so that it contains 10% by weight or less of particles having a particle size of 710 μm or more and 10% by weight or less of particles having a particle size of 150 μm or less; and crosslinking the surface of the base resin in the presence of a surface crosslinking agent (step 5). The superabsorbent resin satisfies the above-mentioned water retention capacity, water-soluble components measured after swelling for 16 hours, water absorption rate, and bulk density.

[0058] Hereinafter, each step of the method for producing a highly water-absorbent resin according to one embodiment will be described in detail.

[0059] (Stage 1) In one embodiment of the method, the step 1 is a step of preparing a monomer composition including an acrylic acid monomer having an acid group, at least a part of which has been neutralized, and an internal crosslinking agent, and crosslinking the monomer composition in the presence of hydrophobic particles to prepare a hydrogel polymer. The acrylic acid monomer and the internal crosslinking agent are described above.

[0060] In the monomer composition, the internal crosslinking agent can be used in an amount of 0.01 to 5 parts by weight based on 100 parts by weight of the acrylic acid monomer. For example, the internal crosslinking agent can be used in an amount of 0.01 parts by weight or more, 0.05 parts by weight or more, 0.1 parts by weight or more, or 0.45 parts by weight or more and 5 parts by weight or less, 3 parts by weight or less, 2 parts by weight or less, 1 part by weight or less, or 0.7 parts by weight or less based on 100 parts by weight of the acrylic acid monomer. If the content of the internal crosslinking agent is too low, crosslinking may not occur sufficiently, making it difficult to achieve strength above an appropriate level, and if the content of the internal crosslinking agent is too high, the internal crosslinking density may increase, making it difficult to achieve the desired water retention ability.

[0061] In addition, the monomer composition may further include a polymerization initiator for initiating a polymerization reaction of the monomer. The polymerization initiator is not particularly limited as long as it is one that is generally used in the production of a highly water-absorbent resin.

[0062] Specifically, the polymerization initiator may be a thermal polymerization initiator or a photopolymerization initiator by UV irradiation depending on the polymerization method. However, even in the photopolymerization method, a certain amount of heat is generated by irradiation with ultraviolet rays, etc., and a certain amount of heat is generated by the progress of the polymerization reaction, which is an exothermic reaction, so a thermal polymerization initiator may also be included.

[0063] The photopolymerization initiator can be any compound capable of forming radicals by the action of light such as ultraviolet light, and is not limited in its composition.

[0064] The photopolymerization initiator may be one or more selected from the group consisting of benzoin ether, dialkyl acetophenone, hydroxyl alkyl ketone, phenyl glyoxylate, benzyl dimethyl ketal, acyl phosphine, and α-aminoketone. Meanwhile, as a specific example of acyl phosphine, commercially available lucirin TPO, i.e., diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide, may be used. More various photoinitiators are well described in "UV Coatings: Basics, Recent Developments and New Application" by Reinhold Schwalm (Elsevier, 2007), p. 115, and are not limited to the above examples.

[0065] The photopolymerization initiator may be contained in a concentration of about 0.01 to about 1.0% by weight based on the monomer composition. If the concentration of the photopolymerization initiator is too low, the polymerization rate may be slow, and if the concentration of the photopolymerization initiator is too high, the molecular weight of the superabsorbent resin may be small, resulting in non-uniform physical properties.

[0066] The thermal polymerization initiator may be one or more selected from the group consisting of persulfate initiators, azo initiators, hydrogen peroxide, and ascorbic acid. Specifically, examples of persulfate initiators include sodium persulfate (Na2S2O8), potassium persulfate (K2S2O8), and ammonium persulfate ((NH4)2S2O8). Examples of azo initiators include 2,2-azobis(2-amidinopropane) dihydrochloride, 2,2-azobis-(N,N-dimethylene)isobutyramidine dihydrochloride, and the like. dihydrochloride, 2-(carbamoylazo)isobutylonitrile, 2,2-azobis[2-(2-imidazolin-2-yl)propane]dihydrochloride, 4,4-azobis-(4-cyanovaleric acid), etc. More diverse thermal polymerization initiators are clearly described in "Principle of Polymerization" by Odian (Wiley, 1981), p. 203, and are not limited to the above examples.

[0067] The thermal polymerization initiator may be included in an amount of 0.001 to 0.2 parts by weight based on 100 parts by weight of the acrylic acid monomer. More preferably, the thermal polymerization initiator may be included in an amount of 0.19 parts by weight or less, 0.18 parts by weight or less, 0.17 parts by weight or less, or 0.16 parts by weight or less. If the concentration of the thermal polymerization initiator is too low, additional thermal polymerization hardly occurs, the effect of adding the thermal polymerization initiator is small, and the content of water-soluble components increases, which may result in a decrease in the pressure property (AUP) relative to the water absorption capacity. If the concentration of the thermal polymerization initiator is too high, the molecular weight of the superabsorbent resin may decrease, which may result in a decrease in the water absorption capacity and the water absorption capacity under pressure property (AUP).

[0068] The polymerization initiator can be used at 1 part by weight or less per 100 parts by weight of the acrylic acid monomer. That is, if the concentration of the polymerization initiator is too low, the polymerization rate is slowed down and a large amount of residual monomer may be extracted in the final product, which is not preferable. On the other hand, if the concentration of the polymerization initiator is higher than the above range, the polymer chains forming the network are shortened, the content of water-soluble components is increased, and the physical properties of the resin, such as the water absorption capacity under pressure, may be reduced, which is not preferable.

[0069] The monomer composition may further contain additives such as a thickener, a plasticizer, a storage stabilizer, and an antioxidant, if necessary.

[0070] The monomer composition containing the monomer may be in a solution state dissolved in a solvent such as water, and the solid content in the monomer composition in such a solution state, that is, the concentration of the monomer, the internal crosslinking agent, and the polymerization initiator, can be appropriately adjusted in consideration of the polymerization time, reaction conditions, etc. For example, the solid content in the monomer composition may be 10 to 80% by weight, or 15 to 60% by weight, or 30 to 50% by weight.

[0071] When the monomer composition has a solid content in this range, it is possible to eliminate the need to remove unreacted monomers after polymerization by utilizing the gel effect phenomenon that occurs in the polymerization reaction of a high-concentration aqueous solution, and it may be advantageous to adjust the pulverization efficiency when pulverizing the polymer described below.

[0072] The solvent that can be used in this case is not limited in composition as long as it can dissolve the above-mentioned components. For example, one or more selected from water, ethanol, ethylene glycol, diethylene glycol, triethylene glycol, 1,4-butanediol, propylene glycol, ethylene glycol monobutyl ether, propylene glycol monomethyl ether, propylene glycol monomethyl ether acetate, methyl ethyl ketone, acetone, methyl amyl ketone, cyclohexanone, cyclopentanone, diethylene glycol monomethyl ether, diethylene glycol ethyl ether, toluene, xylene, butyrolactone, carbitol, methyl cellosolve acetate, and N,N-dimethylacetamide can be used in combination.

[0073] In addition, in step 1, the monomer composition is cross-linked and polymerized in the presence of hydrophobic particles to prepare a hydrogel polymer. The hydrophobic particles may be present in the form of an aqueous dispersion, and a carbonate-based foaming agent may be additionally present in the hydrogel polymer preparation step. When a carbonate-based foaming agent is present, carbon dioxide bubbles are generated from the carbonate-based foaming agent in the above step, and the hydrophobic particles dispersed in water effectively capture the bubbles, thereby increasing the specific surface area of ​​the prepared hydrogel polymer.

[0074] Meanwhile, a bubble generator is used instead of the foaming agent. As such a bubble generator, any microbubble generator that has been used for foaming a monomer composition in a process for producing a superabsorbent resin can be used without any particular limitation. One example of such a microbubble generator may be one in which the monomer composition is passed through a tubular flow path having a plurality of protruding pins mounted therein at a predetermined supply speed, for example, 50 to 1500 (L / min), and the monomer composition is caused to collide with the protruding pins to foam. One example of such a microbubble generator is disclosed in Korean Patent Publication No. 2020-0128969, and it is of course possible to obtain and apply a commercial product applied in the examples described below.

[0075] Here, hydrophobic particles refer to water-insoluble particles that have a contact angle with water of 50° or more or that do not dissolve in water. Particles with a contact angle with water of less than 50° and water-soluble particles may dissolve in the monomer composition in the form of an aqueous solution, making it difficult to capture bubbles generated during the polymerization process, whereas hydrophobic particles are located at the interface between the neutralization liquid and bubbles of carbon dioxide or other gases that exhibit hydrophobicity inside the neutralization liquid, and can effectively capture and stabilize the bubbles.

[0076] Therefore, the hydrophobic particles have a contact angle with water of 50° or more. More specifically, the hydrophobic particles may have a contact angle with water of 70° or more, 100° or more, 120° or more, or 130° or more and 175° or less.

[0077] At this time, the contact angle of the hydrophobic particles can be measured by the following method. First, a coating liquid is prepared by dispersing the hydrophobic particles in a methylene chloride solvent to a concentration of 5% by weight. Next, the coating liquid is spin-coated on a wafer with no surface roughness, and then dried at room temperature to remove the remaining solvent. Then, water is dropped dropwise onto the coating layer, and the contact angle is measured, which is defined as the contact angle of each hydrophobic particle.

[0078] In addition, the hydrophobic particles have an average particle size of 0.2 μm to 50 μm, but if the average particle size of the hydrophobic particles is less than 0.2 μm, it is difficult to effectively capture bubbles generated during the manufacturing process, and uniform pores are not formed, and if the average particle size of the hydrophobic particles exceeds 50 μm, the size of the pores formed may be too large, making it difficult to improve the water absorption rate of the superabsorbent resin. Specifically, for example, the hydrophobic particles may have an average particle size (μm) of 0.3 or more, 0.5 or more, 1 or more, 2 or more, or 3 or more, and 40 or less, 35 or less, or 30 or less.

[0079] Here, the average particle size of the hydrophobic particles means D50, and the "particle size Dn" means the particle size at n% of the cumulative particle number distribution according to the particle size. That is, D50 is the particle size at 50% of the cumulative particle number distribution according to the particle size, D90 is the particle size at 90% of the cumulative particle number distribution according to the particle size, and D10 is the particle size at 10% of the cumulative particle number distribution according to the particle size. The Dn can be measured using a laser diffraction method. Specifically, the powder to be measured is dispersed in a dispersion medium, and then introduced into a commercially available laser diffraction particle size measuring device (e.g., Microtrac S3500). When the particles pass through a laser beam, the difference in the diffraction pattern according to the particle size is measured to calculate the particle size distribution. D10, D50, and D90 can be measured by calculating the particle sizes at 10%, 50%, and 90% of the cumulative particle number distribution according to the particle size in the measuring device.

[0080] Such hydrophobic particles may be one or more types selected from the group consisting of hydrophobic silica, metal salts of fatty acids having 7 to 24 carbon atoms, and hydrophobic organic particles.

[0081] Here, hydrophobic silica is a general term for silica that has a low content of silanol (-SiOH) on the surface and has a contact angle with water of 50° or more, and any hydrophobic silica known in the art can be used without limitation.

[0082] In addition, the metal salt of a fatty acid having 7 to 24 carbon atoms refers to a compound in which a metal cation is bonded in place of a hydrogen ion of a carboxyl group at the end of an unsaturated or saturated fatty acid having 7 to 24 carbon atoms in the molecule and a linear structure, and in this case, the metal salt may be a monovalent metal salt or a polyvalent metal salt having a valence of 2 or more. In this case, when the hydrophobic particles are metal salts of fatty acids having less than 7 carbon atoms, air bubbles that are ionized in an aqueous solution and generated in the form of particles cannot be captured, and when the hydrophobic particles are metal salts of fatty acids having more than 24 carbon atoms, the fatty acid chains become long and dispersion may be difficult.

[0083] Specifically, when the metal salt of the fatty acid is a monovalent metal salt, it has a structure in which one fatty acid carboxylate anion is bound to an alkali ion, which is a monovalent metal cation, and when the metal salt of the fatty acid is a polyvalent metal salt, which is divalent or higher, it has a structure in which fatty acid carboxylate anions are bound to a metal cation in the number of valences of the metal cation.

[0084] In one embodiment, the hydrophobic particles may be a metal salt of a saturated fatty acid having 12 to 20 carbon atoms. For example, the hydrophobic particles may be one or more metal salts of saturated fatty acids selected from the group consisting of a metal salt of lauric acid containing 12 carbon atoms in the molecule, a metal salt of tridecylic acid containing 13 carbon atoms in the molecule, a metal salt of myristic acid containing 14 carbon atoms in the molecule, a metal salt of pentadecanoic acid containing 15 carbon atoms in the molecule, a metal salt of palmitic acid containing 16 carbon atoms in the molecule, a metal salt of margaric acid containing 17 carbon atoms in the molecule, a metal salt of stearic acid containing 18 carbon atoms in the molecule, a metal salt of nonadecylic acid containing 19 carbon atoms in the molecule, and a metal salt of arachidic acid containing 20 carbon atoms in the molecule.

[0085] Preferably, the metal salt of a fatty acid may be a metal stearate, for example one or more metal salts of stearic acid selected from the group consisting of calcium stearate, magnesium stearate, sodium stearate, zinc stearate and potassium stearate.

[0086] The hydrophobic organic particles may be one or more hydrophobic polymer particles selected from the group consisting of ethylene polymers, propylene polymers, styrene polymers, butadiene polymers, styrene-butadiene copolymers, alkyl acrylate polymers, alkyl methacrylate polymers, alkyl acrylate-acrylonitrile copolymers, acrylonitrile-butadiene copolymers, acrylonitrile-butadiene copolymers, acrylonitrile-alkyl acrylate-styrene copolymers, alkyl methacrylate-butadiene-styrene copolymers, and alkyl acrylate-alkyl methacrylate copolymers.

[0087] The hydrophobic particles may be contained in the aqueous dispersion in an amount of 10 to 70% by weight based on the total weight of the aqueous dispersion. If the content of the hydrophobic particles in the aqueous dispersion is too low or too high, the hydrophobic particles may not be stabilized in dispersion, and may aggregate with each other or settle due to gravity.

[0088] In addition, as the surfactant that serves to disperse the hydrophobic particles in the hydrophobic particle aqueous dispersion, any surfactant known in the art that can stabilize the dispersion of the hydrophobic particles can be used without limitation. For example, the surfactant can be one or more surfactants selected from the group consisting of cationic surfactants, anionic surfactants, amphoteric surfactants, and nonionic surfactants. Preferably, in terms of stabilizing the dispersion of the hydrophobic particles, two or more surfactants can be used. More specifically, in consideration of the form of the hydrophobic particles, for example, the form of a metal salt of a saturated fatty acid, a nonionic surfactant and an anionic surfactant, for example, a nonionic surfactant bonded to a long-chain hydrocarbon having 10 or more carbon atoms and a sulfate-based anionic surfactant, can be used together to more effectively disperse the hydrophobic particles in water.

[0089] As an example, the cationic surfactant may include dialkyldimethylammonium salts, alkylbenzylmethylammonium salts, etc.; the anionic surfactant may include alkyl polyoxyethylene sulfates, monoalkyl sulfates, alkylbenzene sulfonates, monoalkyl phosphates, sulfates having a functional group containing a long chain hydrocarbon or a sodium salt thereof, such as sodium lauryl sulfate, sodium dodecyl sulfate, or sodium laureth sulfate; the amphoteric surfactant may include alkyl sulfobetaines, alkyl carboxybetaines, etc.; and the nonionic surfactant may include polyoxyethylene alkyl ethers such as polyethylene glycol, polyoxyalkylene alkylphenyl ethers, polyoxyethylene arylphenyl ethers, fatty acid esters such as sorbitan monopalmitate, fatty acid sorbitan esters, or glycerin monostearate, alkyl monoglyceryl ethers, alkanolamides, alkyl polyglucosides, etc., but is not limited thereto.

[0090] The hydrophobic particle aqueous dispersion may have a pH of 7 or more. If the hydrophobic particle aqueous dispersion has a pH of less than 7, it is not preferable because the aqueous dispersion exhibits acidity and it is difficult to stabilize the hydrophobic particles, which are metal salts of fatty acids.

[0091] Meanwhile, the hydrophobic particles are used in an amount of 0.01 to 0.5 parts by weight based on 100 parts by weight of the acrylic acid monomer. If the content of the hydrophobic particles is too low, the bubble stabilizing effect may be insufficient, and the water absorption speed may be slow. If the content of the hydrophobic particles is too high, the amount of surfactant used to stabilize the hydrophobic particles in the hydrophobic particle aqueous dispersion may increase, and the surface tension may be reduced. For example, the hydrophobic particles may be used in an amount of 0.01 or more, 0.03 or more, 0.05 or more, or 0.08 or more, and 0.5 parts by weight or less, 0.4 parts by weight or less, 0.3 parts by weight or less, or 0.2 parts by weight or less based on 100 parts by weight of the acrylic acid monomer.

[0092] In addition, the carbonate-based foaming agent plays a role in increasing the surface area by forming pores in the hydrogel polymer as foaming occurs during polymerization, and one or more types selected from the group consisting of sodium bicarbonate, sodium carbonate, potassium bicarbonate, potassium carbonate, calcium bicarbonate, calcium carbonate, magnesium bicarbonate, and magnesium carbonate can be used.

[0093] The carbonate-based blowing agent can be used in an amount of 0.005 to 1 part by weight based on 100 parts by weight of the acrylic acid-based monomer. If the content of the blowing agent is less than 0.005 parts by weight, the role of the blowing agent is slight, and if the content of the blowing agent is more than 1 part by weight, the crosslinked polymer has too many pores, the gel strength of the produced superabsorbent resin is reduced, and the density is low, which may cause problems in distribution and storage. For example, the carbonate-based blowing agent may be 0.01 parts by weight or more, 0.05 parts by weight or more, and 0.5 parts by weight or less, 0.3 parts by weight or less, or 0.2 parts by weight or less based on 100 parts by weight of the acrylic acid-based monomer.

[0094] In addition, the carbonate-based foaming agent and the hydrophobic particles can be used in a weight ratio of 1:0.1 to 1:2. When the hydrophobic particles are used at an excessively low content compared to the carbonate-based foaming agent, it is difficult to effectively capture the generated bubbles, and when the hydrophobic particles are used at an excessively high content compared to the foaming agent, various physical properties such as water retention capacity and water absorption rate may be reduced. Specifically, the carbonate-based foaming agent and the hydrophobic particles can be used in a weight ratio of 1:0.4 or more, 1:0.6 or more, or 1:0.8 or more, and 1:1.7 or less, 1:1.5 or less, or 1:1.2 or less. As an example, the carbonate-based foaming agent and the hydrophobic particles can be used in a weight ratio of 1:1.

[0095] Also, surfactants such as alkyl sulfate compounds and polyoxyethylene alkyl ether compounds, which are generally used as foam stabilizers, may not be used in step 1. For example, cationic surfactants such as quaternary ammonium compounds such as dodecyltrimethylammonium chloride and dodecyltrimethylammonium bromide; anionic surfactants such as alkyl sulfate compounds such as sodium dodecyl sulfate, ammonium lauryl sulfate, sodium lauryl ether sulfate, and sodium myreth sulfate; or nonionic surfactants such as alkyl ether sulfate compounds such as polyoxyethylene lauryl ether may not be used in step 1 and step 2. This can prevent the problem of the surface tension of the superabsorbent resin decreasing due to the use of the surfactants.

[0096] On the other hand, the polymerization of the monomer composition in the presence of such an aqueous dispersion of hydrophobic particles and a carbonate-based blowing agent is not particularly limited as long as it is a commonly used polymerization method.

[0097] Specifically, polymerization methods are largely divided into thermal polymerization and photopolymerization depending on the polymerization energy source. In general, when thermal polymerization is carried out, it may be carried out in a reactor having a stirring shaft such as a kneader, and when photopolymerization is carried out, it may be carried out in a reactor equipped with a movable conveyor belt. However, the above-mentioned polymerization methods are merely examples, and the present invention is not limited to the above-mentioned polymerization methods.

[0098] For example, the hydrogel polymer obtained by thermal polymerization by supplying hot air to a reactor such as a kneader equipped with an agitator shaft as described above or by heating the reactor may be in the form of a hydrogel polymer discharged from the outlet of the reactor, which may be in the form of several centimeters to several millimeters, depending on the form of the agitator shaft equipped in the reactor. Specifically, the size of the obtained hydrogel polymer may vary depending on the concentration of the monomer composition injected and the injection speed, but a hydrogel polymer having a weight average particle size of 2 to 50 mm is usually obtained.

[0099] In addition, when photopolymerization is carried out in a reactor equipped with a movable conveyor belt as described above, the form of the hydrogel polymer obtained may be a sheet-like hydrogel polymer having the width of the belt. In this case, the thickness of the polymer sheet varies depending on the concentration and injection speed of the monomer composition injected, but it is preferable to supply the monomer composition so that a sheet-like polymer having a thickness of about 0.5 to about 5 cm is obtained. If the monomer composition is supplied so that the thickness of the sheet-like polymer is too thin, the production efficiency is low, which is undesirable, and if the thickness of the sheet-like polymer exceeds 5 cm, the polymerization reaction may not occur evenly over the entire thickness due to the excessively thick thickness.

[0100] The water content of the hydrogel polymer obtained by this method may be about 40 to about 80% by weight. Meanwhile, throughout this specification, the term "water content" refers to the water content relative to the weight of the entire polymer, and is calculated by subtracting the weight of the polymer in a dry state from the weight of the polymer. Specifically, it is defined as a value calculated by measuring the weight loss due to the evaporation of water in the polymer during the process of drying the polymer by increasing the temperature by infrared heating. Here, the drying conditions are a method of increasing the temperature from room temperature to about 180°C and then maintaining it at 180°C, and the total drying time is set to 20 minutes, including 5 minutes for the temperature increase step, and the water content is measured.

[0101] (Stage 2) Next, the hydrogel polymer is dried to form a powdered base resin, and if necessary, a coarse pulverization step may be performed before drying to increase the efficiency of the drying step.

[0102] The coarse pulverization process is a process for increasing the drying efficiency in the subsequent drying process and controlling the particle size of the produced superabsorbent resin powder. The pulverizer used here is not limited in terms of configuration, and specifically may include any one selected from the group of pulverizing devices consisting of a vertical pulverizer, a turbo cutter, a turbo grinder, a rotary cutter mill, a cutter mill, a disc mill, a shred crusher, a crusher, a meat chopper, and a disc cutter, but is not limited to the above examples.

[0103] The gel crushing of the hydrogel polymer may be performed so that the particle size of the hydrogel polymer is 0.01 mm to 50 mm, or 0.01 mm to 30 mm. That is, in order to increase the drying efficiency, the hydrogel polymer is preferably crushed into particles of 50 mm or less. However, since excessive crushing may cause aggregation between particles, the hydrogel polymer is preferably gel crushed into particles of 0.01 mm or more.

[0104] In addition, since the gel crushing of the hydrogel polymer is performed in a state where the water content is relatively low, the hydrogel polymer may stick to the surface of the gel crusher. In order to minimize this phenomenon, steam, water, a surfactant, an anti-aggregating agent (e.g., clay, silica, etc.), a persulfate initiator, an azo initiator, hydrogen peroxide, a thermal polymerization initiator, an epoxy crosslinking agent, a diol crosslinking agent, a crosslinking agent containing an acrylate having a multifunctional group with two or more functional groups, a crosslinking agent containing a monofunctional group with a hydroxyl group, etc. may be added to the hydrogel polymer as necessary.

[0105] The polymer immediately after polymerization, which has been chopped and pulverized as described above or has not been subjected to the chopping and pulverization step, is dried. At this time, the drying temperature in the drying step may be about 150 to about 250°C. If the drying temperature is less than 150°C, the drying time may be excessively long, and the physical properties of the superabsorbent resin finally formed may be deteriorated. If the drying temperature exceeds 250°C, only the surface of the polymer may be excessively dried, and fine powder may be generated in the subsequent pulverization step, and the physical properties of the superabsorbent resin finally formed may be deteriorated. Therefore, the drying may be preferably performed at a temperature of about 150 to about 200°C, more preferably at a temperature of about 160 to about 180°C.

[0106] Meanwhile, the drying time may be about 20 to about 90 minutes in consideration of process efficiency, but is not limited thereto.

[0107] The drying method in the drying step can be selected and used without any limitation on the configuration as long as it is one that is usually used in the drying process of a hydrogel polymer. Specifically, the drying step can be carried out by a method such as hot air supply, infrared radiation, ultrashort wave radiation, or ultraviolet radiation. The water content of the polymer after such a drying step may be about 0.1 to about 5% by weight.

[0108] (Stage 3 & Stage 4) The base resin powder is then ground to a particle size distribution in a first grinding step (step 3) and a second grinding step (step 4). If necessary, a drying step may be included before performing step 3 or before performing step 4.

[0109] Specifically, in step 3, the base resin powder is pulverized (first pulverization step) so that it contains 50% by weight or more of particles with a particle size of 710 μm or more, and in step 4, the base resin powder that has been subjected to the first pulverization step is pulverized (second pulverization step) so that it contains 10% by weight or less of particles with a particle size of 710 μm or more and 10% by weight or less of particles with a particle size of 150 μm or less.

[0110] Specifically, regardless of the type of pulverizer, the classification process after the primary pulverization stage results in particles of 710 μm or more being contained at 50% by weight or more. Particles of 710 μm or more undergo a separate secondary pulverization process, and the particle size of the base resin powder obtained by the primary and secondary pulverization is such that particles of 710 μm to 850 μm or less are contained at 10% by weight or less, and particles of 150 μm or less are contained at 10% by weight or less.

[0111] After the primary pulverization, the pulverizer conditions can be adjusted so that particles of 710 μm or more are contained at 50% by weight or more. When a coarse pulverizer is used, the degree of pulverization can be adjusted by the rpm of the pulverizer, and when a roll mill is used, the primary pulverization can be performed by adjusting the gap between the roll mills. The resin obtained by the primary pulverization is classified, and a classification mesh can be configured so that particles of 710 μm or more can be separated by the classification process. Particles of 710 μm or more are subjected to a secondary pulverization process. The secondary pulverization process can be applied regardless of the type of pulverizer, as in the primary pulverization. The secondary pulverization process can be included in the base resin by the classification process or without the classification process, but the particle size of the final base resin powder should be such that particles of 710 μm to 850 μm or less are contained at 10% by weight or less, and particles of 150 μm or less are contained at 10% by weight or less.

[0112] When a hydrogel having a high water absorption rate is dried and subjected to only primary grinding so that the final base resin powder contains 10% by weight or less of particles having a particle size of 710 μm or more and 850 μm or less, and 10% by weight or less of particles having a particle size of 150 μm or less, the bulk density may be low.

[0113] Preferably, the base resin powder after the first grinding step has a bulk density of 0.50 g / ml or less.

[0114] The base resin, which is a polymer powder obtained after the pulverization step, may have a particle size of about 150 to about 850 μm. Specifically, the pulverizer used to pulverize to such a particle size may be a pin mill, a hammer mill, a screw mill, a roll mill, a disc mill, or a jog mill, but the present invention is not limited to the above examples.

[0115] After the pulverization step, the base resin obtained after pulverization is classified according to particle size in order to control the physical properties of the superabsorbent resin powder that is the final product. Preferably, polymers having a particle size of about 150 to about 850 μm are classified, and only the base resin having such a particle size can undergo the surface crosslinking reaction step. Such particle size can be measured according to the EDANA WSP220.3 method of the European Disposables and Nonwovens Association (EDANA).

[0116] (Stage 5) On the other hand, after the base resin powder is produced through the above-mentioned classification process, the base resin powder can be surface-crosslinked while being heat-treated in the presence of a surface crosslinking agent to form highly water-absorbent resin particles. The surface crosslinking induces a crosslinking reaction on the surface of the base resin powder in the presence of a surface crosslinking agent, and such surface crosslinking can form a surface modified layer (surface crosslinked layer) on the surface of the base resin powder.

[0117] The content of the surface cross-linking agent can be appropriately selected depending on the type of the surface cross-linking agent to be added and the reaction conditions, and can be about 0.001 to about 5 parts by weight per 100 parts by weight of the base resin. If the content of the surface cross-linking agent is too low, the surface modification may not be performed well, and the physical properties of the final resin may be deteriorated. On the contrary, if an excessive surface cross-linking agent is used, the basic water absorption performance of the resin may be deteriorated due to an excessive surface cross-linking reaction, which is not preferable.

[0118] There is no limitation on the constitution of the method for mixing the surface crosslinking agent with the base resin. A method of putting the surface crosslinking agent and the base resin powder in a reaction tank and mixing them, a method of spraying the surface crosslinking agent onto the base resin powder, a method of continuously supplying the base resin and the surface crosslinking agent to a continuously operating mixer and mixing them, etc. can be used.

[0119] When the surface crosslinking agent is added, it may be added in the form of a surface crosslinking solution by mixing with water. When water is added, it has an advantage that the surface crosslinking agent can be uniformly dispersed in the polymer. At this time, the content of the added water is preferably about 1 to about 10 parts by weight per 100 parts by weight of the base resin in order to induce uniform dispersion of the surface crosslinking agent, prevent the polymer powder from clumping, and optimize the surface penetration depth of the surface crosslinking agent.

[0120] The above-mentioned surface crosslinking step can be carried out by further using, in addition to the surface crosslinking agent, one or more selected from the group consisting of a polyvalent metal salt, for example, an aluminum salt, more specifically, a sulfate salt, a potassium salt, an ammonium salt, a sodium salt, and a hydrochloride salt of aluminum.

[0121] By additionally using such a polyvalent metal salt, the liquid permeability of the superabsorbent resin produced by the method of one embodiment can be further improved. Such a polyvalent metal salt may be added to the surface crosslinking solution together with the surface crosslinking agent, and may be used in an amount of 0.01 to 4 parts by weight based on 100 parts by weight of the base resin powder.

[0122] In addition, in order to achieve uniform surface cross-linking, the surface cross-linking liquid containing the surface cross-linking agent and the liquid medium may further contain, optionally, a surfactant, a polycarboxylic acid copolymer having repeating units represented by the following chemical formula 1-a and chemical formula 1-b, or an aliphatic alcohol having 6 or more carbon atoms. In this way, by using multiple types of surface cross-linking agents and selectively using additional components contained in the surface cross-linking liquid, the surface tension of the surface cross-linking liquid is achieved in a specific range that is relatively low, and a superabsorbent resin having the above-mentioned physical properties of one embodiment can be produced:

[0123] [ka]

[0124] In the above chemical formulas 1-a and 1-b, R 1 , R 2 and R 3 are each independently a hydrogen atom or an alkyl group having 1 to 6 carbon atoms, RO is an oxyalkylene group having 2 to 4 carbon atoms, and M 1 is hydrogen or a monovalent metal or nonmetal ion, X is -COO-, an alkyloxy group having 1 to 5 carbon atoms or an alkyldioxy group having 1 to 5 carbon atoms, m is an integer of 1 to 100, n is an integer of 1 to 1000, and p is an integer of 1 to 150, and when p is 2 or more, -RO- repeated 2 or more times may be the same or different.

[0125] Meanwhile, the surface crosslinking process can be carried out using a surface crosslinking liquid containing water and / or a hydrophilic organic solvent (e.g., an alcohol-based polar organic solvent such as methanol) as a liquid medium together with the above-mentioned surface crosslinking agent, etc. At this time, the content of water and the hydrophilic organic solvent can be adjusted and applied by adjusting the addition ratio with respect to 100 parts by weight of the base resin powder in order to induce uniform dispersion of the surface crosslinking liquid, prevent the agglomeration phenomenon of the base resin powder, and at the same time, optimize the surface penetration depth of the surface crosslinking agent.

[0126] Regarding the method of adding the above-mentioned surface cross-linking liquid to the base resin powder, there is no particular limitation on the constitution. For example, the surface cross-linking liquid and the base resin powder are put into a reaction tank and mixed, the surface cross-linking liquid is sprayed onto the base resin powder, or the base resin powder and the surface cross-linking liquid are continuously supplied to a continuously operating mixer and mixed therewith, and the like can be used.

[0127] Specifically, the surface crosslinking may be performed by heating the base resin powder to which the surface crosslinking liquid has been added from an initial temperature of 20°C to 130°C over a period of 10 to 30 minutes to a maximum temperature of 140°C to 200°C, and maintaining the maximum temperature for 5 to 60 minutes. More specifically, the surface crosslinking may be performed by maintaining a maximum temperature of 140°C to 200°C or 170°C to 195°C for 5 to 60 minutes, or 10 to 50 minutes.

[0128] By satisfying such surface cross-linking process conditions (particularly, the temperature rise conditions and the reaction conditions at the maximum reaction temperature), a highly water-absorbent resin that adequately satisfies the physical properties of one embodiment can be more effectively produced.

[0129] The temperature raising means for the surface cross-linking reaction is not particularly limited. Heating can be performed by supplying a heat medium or directly supplying a heat source. At this time, the type of heat medium that can be used can be a heated fluid such as steam, hot air, hot oil, etc., but is not limited thereto, and the temperature of the heat medium to be supplied can be appropriately selected in consideration of the means of the heat medium, the heating rate, and the target temperature of the heat medium to be supplied. On the other hand, examples of the heat source to be directly supplied include heating by electricity and heating by gas, but are not limited to the above examples. As described above, after forming a surface cross-linked layer on the surface of the base resin, an inorganic substance can be further mixed additionally.

[0130] The inorganic material may be, for example, one or more selected from the group consisting of silica, clay, alumina, a silica-alumina composite, and titania, and preferably, silica.

[0131] Such inorganic substances can be used in an amount of 0.01 parts by weight or more, or 0.05 parts by weight or more, or 0.1 parts by weight or more, and 5 parts by weight or less, or 3 parts by weight or less, or 1 part by weight or less, per 100 parts by weight of the superabsorbent resin.

[0132] The superabsorbent polymer obtained by the above-mentioned manufacturing method maintains excellent water absorption performance such as water retention capacity and pressurized water absorption capacity, meets improved water absorption speed, and has excellent rewetting properties, so that it can meet the various physical properties of one embodiment. Therefore, a sanitary product containing the superabsorbent polymer can be provided. As an example, the superabsorbent polymer can be suitably used in sanitary products such as diapers, particularly ultra-thin sanitary products with a reduced pulp content.

[0133] The present invention will be described in more detail below for a better understanding of the present invention. However, the following examples are merely illustrative of the present invention, and the content of the present invention is not limited to the following examples.

[0134] Production Example 1: Production of hydrophobic silica aqueous dispersion 100g of water was put into a high shear mixer, and while stirring at 5000 rpm, hydrophobic silica with an average particle size of 0.3 μm and a contact angle with water of 130° and hydrophobic silica with an average particle size of 3 μm and a contact angle with water of 130° were dispersed at 0.2 wt% and 2 wt% based on the total weight of the final aqueous dispersion, respectively, and gradually added. When the silica was completely added, the mixture was stirred at 8000 rpm at a temperature of 45° C. for 30 minutes. At this time, the pH of the obtained hydrophobic silica aqueous dispersion was 9.

[0135] Example 1 (Step 1) 100 parts by weight of acrylic acid was mixed with 0.01 parts by weight of PEGDA400 (polyethylene glycol diacrylate 400) as an internal crosslinking agent and 0.1 parts by weight of phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide as a photoinitiator to prepare a monomer solution. Next, while continuously supplying the monomer solution with a metering pump, 160 parts by weight of 24% by weight sodium hydroxide aqueous solution was continuously added, and 3 parts by weight of 4% by weight sodium persulfate aqueous solution, 5 parts by weight of 4% by weight ethylene glycol diglycidyl ether (EJ1030s), 5 parts by weight of 4% by weight sodium bicarbonate aqueous solution, and 5 parts by weight of hydrophobic silica aqueous dispersion containing 0.2% by weight of hydrophobic silica having an average particle size of 0.3 μm and 2% by weight of hydrophobic silica having an average particle size of 3 μm prepared in Preparation Example 1 were mixed at high speed to prepare a monomer composition. By this transfer, the monomer composition was fed into a polymerization reactor consisting of a moving conveyor belt, and UV polymerization was carried out for 3 minutes by irradiating it with ultraviolet light using a UV irradiation device, thereby producing a sheet-like hydrogel polymer.

[0136] (Step 2) The hydrogel polymer was cut into pieces with an average size of about 300 mm or less, and then fed into a crusher (equipped with a perforated plate containing a plurality of holes with a diameter of 15 mm) to cut the hydrogel. The crushed hydrogel was then dried in a dryer capable of shifting airflow up and down. Hot air at 180°C was blown in such a way that the moisture content of the dried powder was about 5% or less, and the hydrogel was uniformly dried.

[0137] (Step 3) The dried resin was pulverized in a pulverizer and then classified to obtain a base resin with a size of 150 to 850 μm. The pulverizer used was a PULVERISETTE 19 manufactured by FRITSCH. A 12 mm sieve cassette was installed in the pulverizer to perform primary pulverization of the dried hydrogel. Among the following sieves (WS Tylor, 8" STAINLESS-STAINLESS TEST SIEVE), mesh numbers 24 / 32 / 48 / 100 / pan were installed in order, and the pulverized particles were placed on the top of the #24 mesh, fixed to the sieve shaker, and classified at 1.5 amplitude for 10 minutes.

[0138] [Table 1]

[0139] After the classification was completed, the resin content at the top of the #24 mesh was measured, and it was found that the particles contained more than 50% by weight of the dried hydrogel that was added.

[0140] The particles on the top of the #24 mesh were subjected to secondary crushing, and for secondary crushing, a 1.0 mm sieve cassette was installed in the crusher to crush the dried hydrogel. Sieves (WS Tylor, 8" STAINLESS-STAINLESS TEST SIEVE) with mesh numbers 20 / 32 / 48 / 100 / pan were installed in sequence, and the secondary crushed particles were placed on the top of the #20 mesh, fixed to the sieve shaker, and classified at 1.5 amplitude for 10 minutes.

[0141] The weight of the particles after classification can be calculated as follows:

[0142] Particle size distribution by particle size = {(weight of sieve + dried mass after classification) - (weight of empty sieve)} / (dried mass after crushing) x 100

[0143] (Step 4) 8 parts by weight of a surface crosslinking agent aqueous solution containing 1.2 parts by weight of ethylene carbonate, 0.5 parts by weight of propylene carbonate, 0.5 parts by weight of propylene glycol, and 0.5 parts by weight of hydrophilic water-dispersed silica (snotex) was sprayed onto 100 parts by weight of the classified base resin powder, and the mixture was stirred at room temperature to distribute the surface crosslinking liquid evenly on the base resin powder. Next, the base resin powder mixed with the surface crosslinking liquid was placed in a surface crosslinking reactor to carry out a surface crosslinking reaction.

[0144] In the surface crosslinking reactor, the base resin powder was gradually heated from an initial temperature of about 80°C, and was operated so as to reach a maximum reaction temperature of 190°C after 30 minutes. After reaching the maximum reaction temperature, the reaction was continued for an additional 15 minutes, and then a final superabsorbent resin sample was taken. After the surface crosslinking process, the superabsorbent resin of Example 1 having a particle size of 150 μm to 850 μm was produced by classifying the particles using a standard mesh sieve according to the ASTM standard.

[0145] Example 2 A superabsorbent polymer was prepared in the same manner as in Example 1, except that step 4 in Example 1 was carried out as follows.

[0146] A surface crosslinking solution was prepared by mixing 4 parts by weight of water, 1.0 part by weight of propylene glycol, 0.08 parts by weight of ethylene glycol diglycidyl ether, and 0.05 parts by weight of a polycarboxylic acid copolymer (a copolymer of methoxypolyethylene glycol monomethacrylate and methacrylic acid, Mw=40,000) with respect to 100 parts by weight of the base resin. The surface crosslinking solution was sprayed and mixed into 100 parts by weight of the obtained base resin powder, which was then placed in a vessel consisting of a stirrer and a double jacket, and the surface crosslinking reaction was carried out at 140°C for 35 minutes. Thereafter, the surface-treated powder was classified using a standard mesh sieve according to the ASTM standard to obtain a highly water-absorbent resin powder having a particle size of 150 to 850 μm.

[0147] Example 3 A superabsorbent resin was produced in the same manner as in Example 1, except that in step 1 of Example 1, 4 parts by weight of a 4% by weight aqueous solution of sodium persulfate was used.

[0148] Example 4 The superabsorbent resin produced in Example 3 was blended with 0.2 parts by weight of fumed silica (Aerosil 200) to produce a final superabsorbent resin.

[0149] Comparative Example 1 A superabsorbent polymer was prepared in the same manner as in Example 1, except that step 3 in Example 1 was carried out as follows.

[0150] The dried resin was pulverized in a pulverizer and then classified to obtain a base resin with a size of 150 to 850 μm. The pulverizer used was a PULVERISETTE19 manufactured by FRITSCH. A 0.75 mm sieve cassette was installed in the pulverizer to pulverize the dried hydrogel. Among the sieves of Example 1 (WS Tylor, 8" STAINLESS-STAINLESS TEST SIEVE), mesh numbers 20 / 32 / 48 / 100 / pan were installed in sequence, and the pulverized particles were placed on the top end of the #20 mesh, fixed to a sieve shaker, and classified at 1.5 amplitude for 10 minutes. The pulverization step was completed without a second pulverization.

[0151] Comparative Example 2 A superabsorbent polymer was prepared in the same manner as in Example 1, except that step 3 in Example 1 was carried out as follows.

[0152] The dried resin was pulverized in a pulverizer and then classified to obtain a base resin with a size of 150 to 850 μm. The pulverizer used was a PULVERISETTE19 manufactured by FRITSCH. A 2.0 mm sieve cassette was installed in the pulverizer, and the dried hydrogel was subjected to primary pulverization. Among the sieves of Example 1 (WS Tylor, 8" STAINLESS-STAINLESS TEST SIEVE), mesh numbers 20 / 32 / 48 / 100 / pan were installed in sequence, and the pulverized particles were placed on the top end of the #20 mesh, fixed to a sieve shaker, and classified at 1.5 amplitude for 10 minutes, and the pulverization stage was completed without a second pulverization.

[0153] Comparative Example 3 A highly water-absorbent resin was produced in the same manner as in Example 1, except that 0.2 parts by weight of span80 (Sigma-Aldrich) was used instead of the hydrophobic particles.

[0154] Comparative Example 4 A superabsorbent polymer was prepared in the same manner as in Example 1, except that instead of sodium bicarbonate and hydrophobic particles, gas was injected using an air bubble injector, and 0.3 parts by weight of sodium dodecyl sulfate was used.

[0155] Experimental example: Measurement of the physical properties of superabsorbent resin The superabsorbent resins prepared in the above examples and comparative examples were evaluated for physical properties by the following methods, and the results are shown in Table 1. Unless otherwise indicated, all of the following physical property evaluations were carried out at room temperature (23±1°C) and relative humidity of 45±1%, and saline or salt water refers to a 0.9 wt% sodium chloride (NaCl) aqueous solution, and salt water at a temperature of 23±1°C was used.

[0156] (1) Bulk density (g / ml): Measures particles with a diameter of 150-850 μm About 100 g of the superabsorbent resin having the overall particle size distribution of the above-mentioned Examples and Comparative Examples was placed in a funnel-shaped bulk density measuring device, poured into a 100 ml container, and the weight of the superabsorbent resin in the container was measured. The bulk density was calculated by (weight of superabsorbent resin) / (volume of container, 100 ml).

[0157] Bulk density was measured according to the EDANA NWSP251.0.R2 (15) method.

[0158] The density cup used was made of cylindrical stainless steel (ISO / TR15510), had a capacity of (100.0±0.5) ml, an inner diameter of 45.0±0.1 mm, and an internal height of 63.1±0.1 mm.

[0159] The funnel was made of stainless steel, and the detailed design complied with ISO / TR15510. a) It had an orifice internal diameter of (10.00±0.01)mm, an inclination angle of cone generatrix of 20°, and a height of (145.0±0.5)mm.

[0160] Bulk density analysis was measured at (23±2)℃ and (45±15)% relative humidity.

[0161] First, a density cup was placed under the funnel and 100g of SAP was filled into the closed funnel of the orifice. The orifice was opened and a timer was started to measure the time it took for all the SAP to fall out of the funnel. The SAP that overflowed from the density cup was removed and then weighed (W2). The weight of the empty density cup (W1) was measured, and the weight of the SAP in the density cup was calculated by the difference between the two weights.

[0162] Bulk density (ρ, g / ml) is calculated as "ρ = (W2-W1) / 100", where 100 (ml) is the volume of the density cup.

[0163] (2) Water-soluble components measured after swelling for 16 hours (16hr EC,%): Particles with a particle size of 150-850μm were measured. The water-soluble components in the above examples and comparative examples were measured according to the method of EDANA NWSP270.0.R2(15).

[0164] (3) Centrifuge Retention Capacity (CRC, g / g): Measures particles with a diameter of 150-850 μm The water retention capacity of each resin was measured using EDANA NWSP241.0.R2 (15) based on the water absorption capacity under no load.

[0165] Specifically, a superabsorbent resin W0(g) (approximately 0.2g) having a total particle size distribution was uniformly placed in a nonwoven envelope, sealed, and then immersed in physiological saline (0.9% by weight) at room temperature. After 30 minutes, the envelope was centrifuged at 250G for 3 minutes to remove water, and the mass W2(g) of the envelope was measured. The same procedure was also performed without the resin, and the mass W1(g) at that time was measured. Using the obtained masses, the CRC(g / g) was calculated using the following formula.

[0166] [Formula 1] CRC(g / g)={[W2(g)-W1(g)] / W0(g)}-1

[0167] (4) Absorption under pressure (0.7AUP: Absorption Under Pressure, g / g): Measure particles with a particle size of 150-850 μm The water absorption capacity of each resin at 0.7 psi was measured using EDANA NWSP242.0.R2(15).

[0168] Specifically, a stainless steel wire mesh of 400 mesh was attached to the bottom of a plastic cylinder with an inner diameter of 60 mm. Under conditions of room temperature and humidity of 50%, a superabsorbent resin W0(g) (0.90 g) having a total particle size distribution was evenly spread on the wire mesh, and a piston capable of applying a load of 0.7 psi evenly thereon was slightly smaller than the outer diameter of 60 mm, had no gap with the inner wall of the cylinder, and was not hindered from moving up and down. At this time, the weight W3(g) of the device was measured.

[0169] A glass filter with a diameter of 90 mm and a thickness of 5 mm was placed inside a petroleum dish with a diameter of 150 mm, and physiological saline solution consisting of 0.9% by weight of sodium chloride was placed at the same level as the upper surface of the glass filter. A sheet of filter paper with a diameter of 90 mm was placed on top of the glass filter. The measuring device was placed on the filter paper, and the liquid was absorbed under a load for one hour. After one hour, the measuring device was lifted and its weight W4 (g) was measured.

[0170] Using the obtained masses, the water absorption capacity under pressure (g / g) was calculated according to the following formula.

[0171] [Formula 2] AUP(g / g)=[W4(g)-W3(g)] / W0(g)

[0172] (5) Water absorption rate (Vortex time, s): Measures particles of all particle sizes The water absorption rate (vortex time) of the superabsorbent resins of the above examples and comparative examples was measured by the following method.

[0173] (i) First, 50 mL of 0.9% salt water was poured into a 100 mL flat-bottomed beaker using a 100 mL mass cylinder. (ii) Next, the beaker was placed in the center of a magnetic stirrer, and then a cylindrical magnetic bar (diameter×length=8 mm×30 mm) was placed in the beaker. (iii) Thereafter, the stirrer was operated so that the magnetic bar was stirring at 600 rpm, and the lowest part of the vortex generated by stirring was brought into contact with the magnetic bar. (iv) After confirming that the temperature of the salt water in the beaker had reached 24.0°C, a superabsorbent resin sample of 2±0.01 g in terms of the overall particle size distribution was added while simultaneously starting a stopwatch. The time until the vortex disappeared and the liquid surface became completely horizontal was measured in seconds, and this was regarded as the water absorption speed.

[0174] (6) Diaper absorbency core rewet (rewet amount, Rewet, g) The absorbent bodies were manufactured by the following method using the superabsorbent resins of the above-mentioned Examples and Comparative Examples, and the rewetting properties under pressure conditions were evaluated. The manufacturing method of the absorbent bodies is as follows.

[0175] On a first nonwoven fabric (product name: Softhann (registered trademark), manufacturer: Sambo) measuring 350 mm x 100 mm, 0.3 g of adhesive (product name: FLC7228AZP, manufacturer: HB Fuller) (adhesive layer) was uniformly applied using a hot melt sprayer, and then 4.5 g of the superabsorbent resin prepared in the above preparation example was uniformly applied at a feed rate of 2 g / s to prepare a first coating layer of superabsorbent resin. 0.3 g of adhesive was applied thereon to prepare a first coating layer of adhesive. Thereafter, the manufacturing process of the first coating layer of superabsorbent resin and the first coating layer of adhesive was repeated two more times to prepare a second coating layer of superabsorbent resin, a second coating layer of adhesive, a third coating layer of superabsorbent resin, and an adhesive layer, and then a second nonwoven fabric (product name: Softhann (registered trademark), manufacturer: Sambo) was attached to prepare an absorbent. The amount of adhesive used in each adhesive layer was the same at 0.3 g, and the amount of superabsorbent polymer used in each superabsorbent polymer layer was the same at 4.5 g.

[0176] The rewet of each of the prepared absorbents was measured as follows.

[0177] 85 mL of 0.9 wt % sodium chloride aqueous solution (physiological saline) was injected into the center of each absorbent (size 350 mm x 100 mm x 3 mm). After 15 minutes, a weight was placed on the absorbent, and 85 mL of physiological saline was again injected into the same position while applying a pressure of 0.42 psi. After 15 minutes, the weight placed on the absorbent was temporarily removed, and then a paper of size 300 mm x 90 mm (300 gsm filter paper (S-300, Korea Filter Paper), approximately 1.5 g per sheet, W5 (g)) was placed on the absorbent, and the weight was placed on the paper again to position the paper between the absorbent and the weight. After 2 minutes, the amount of salt water seeping out of the absorbent into the paper was measured, and the rewet amount (g) was calculated by the following formula 3.

[0178] [Formula 3] Rewet amount (g) = W6 (g) - W5 (g)

[0179] In the above formula 3, W5 (g) is the initial weight of the paper, and W6 (g) is the weight of the paper that absorbs the liquid that seeps out of the absorbent body under a load (0.42 psi) for 2 minutes after injecting saline into the absorbent body with and without pressure.

[0180] [Table 2]

[0181] As shown in Table 1, in the case of the superabsorbent resin of one embodiment which satisfies the range of water absorption rate, bulk density and water-soluble components measured after swelling for 16 hours, the rewet property is excellent at 1.0 g or less. Therefore, it was confirmed that the superabsorbent resin of the embodiment has the same or better water absorption capacity and water absorption rate as the superabsorbent resin of the comparative example, and also has excellent rewet properties.

Claims

1. A base resin containing an acidic group, at least a portion of which has been neutralized, comprising a crosslinked polymer of an acrylic acid monomer and an internal crosslinking agent; and A superabsorbent resin comprising a surface cross-linked layer formed on the base resin and in which the cross-linked polymer is additionally cross-linked via a surface cross-linking agent, The superabsorbent resin is 1) The water retention capacity (CRC) measured by EDANA NWSP241.0.R2 (15) is 32 g / g to 40 g / g; 2) The water-soluble component after swelling for 16 hours as measured by EDANA NWSP270.0.R2(15) is 10% by weight or less; 3) The water absorption speed (vortex time) by the vortex method is 30 seconds or less; 4) The bulk density measured by EDANA NWSP251.0.R2(15) is 0.55 g / ml or more and 0.65 g / ml or less. Super absorbent resin.

2. The internal crosslinking agent is an epoxy compound or a polyethylene glycol polymer. The highly water-absorbent resin according to claim 1.

3. The highly absorbent resin contains 10% by weight or less of particles having a particle size of 710 μm or more and 850 μm or less. The highly water-absorbent resin according to claim 1.

4. The highly absorbent resin contains 10% by weight or less of particles having a particle size of 150 μm or less. The highly water-absorbent resin according to claim 1.

5. The rewet value of the pulpless absorbent material containing the superabsorbent resin is 1 g or less. The highly water-absorbent resin according to claim 1.

6. A step (step 1) of forming a hydrogel polymer by polymerizing a monomer composition including an acrylic acid monomer having an acid group, at least a portion of which has been neutralized, an internal crosslinking agent, an initiator, and hydrophobic particles; drying the hydrous gel polymer to form a base resin powder (Step 2); a first pulverization step (step 3) of pulverizing the base resin powder so that the base resin powder contains particles having a particle size of 710 μm or more at 50% by weight or more; A second pulverization step (step 4) of pulverizing the base resin powder obtained by the first pulverization step so that the base resin powder contains 10% by weight or less of particles having a particle size of 710 μm or more and 10% by weight or less of particles having a particle size of 150 μm or less; and and crosslinking the surface of the base resin in the presence of a surface crosslinking agent (step 5). A method for producing a superabsorbent resin.

7. The internal crosslinking agent is an epoxy compound or a polyethylene glycol polymer. A method for producing the highly water-absorbent resin according to claim 6.

8. The internal crosslinking agent is contained in an amount of 0.01 part by weight or more based on 100 parts by weight of the acrylic acid monomer. A method for producing the highly water-absorbent resin according to claim 6.

9. The initiator includes a thermal polymerization initiator, The thermal polymerization initiator is contained in an amount of 0.001 to 0.2 parts by weight based on 100 parts by weight of the acrylic acid monomer. A method for producing the highly water-absorbent resin according to claim 6.

10. The bulk density of the base resin powder after the first grinding step is 0.50 g / ml or less. A method for producing the highly water-absorbent resin according to claim 6.

11. The superabsorbent resin is 1) The water retention capacity (CRC) measured by EDANA NWSP241.0.R2 (15) is 32 g / g to 40 g / g; 2) The water-soluble component after swelling for 16 hours as measured by EDANA NWSP270.0.R2(15) is 10% by weight or less; 3) The water absorption speed (vortex time) by the vortex method is 30 seconds or less; 4) The bulk density measured by EDANA NWSP251.0.R2(15) is 0.55 g / ml or more and 0.65 g / ml or less. A method for producing the highly water-absorbent resin according to claim 6.

12. A sanitary product comprising the highly absorbent polymer of claim 1.

Citation Information

Patent Citations

  • Water-absorbing resin particle, absorber and absorbing article using the same, and production method of water-absorbing resin particle

    JP2019141754A